Pro-Environmental Behaviour in Russia. A Systematic Review - Sautkina, E.V.; Agissova, F.B.; Ivanova, A.A.; Ivande, K.S.; Kabanova, V.S. (Èksperimentalʹnaâ psihologiâ, 2022)
Pro-environmental behavior plays one of the most important roles in reducing global environmental change. This systematic review critically analyzes methodology and synthesizes results of 49 empirical studies of pro-environmental behavior in Russia published between 1999 and 2021. Methodological advantages of the studies include the use of primary data and sample sizes. The shortcomings include a lack of experimental studies, the use of self-reports and descriptive data analyses. Recently, however, the methodological quality of studies has been improving. The most common forms of pro-environmental behavior in Russia are: household waste management and reduction, land clearing and greening, resource conservation and eco-consumption. The determinants of pro-environmental behavior include gender (female), level of education (higher), biospheric values, environmental concern, environmental motivation, personal and descriptive norms. The expansion of evidence base on pro-environmental behavior and its determinants in Russia should be accompanied by a wider use of laboratory and natural experiments, and improvements in data collection and analysis methodology. Проэкологическое поведение — один из наиболее важных факторов противостояния глобальным средовым изменениям. В данном систематическом обзоре критически анализируется методология и синтезируются результаты 49 эмпирических исследований проэкологического поведения в России, опубликованных в 1999—2021 гг. Среди методологических преимуществ исследований можно выделить использование первичного эмпирического материала и объем выборок. Среди недостатков — нехватку экспериментальных исследований, использование самоотчетов и дескриптивный анализ данных. В последнее время качество методологии повышается. Наиболее часто встречающимися формами проэкологического поведения в России являются управление и минимизация бытовых отходов, участие в уборке территорий и озеленение, ресурсосбережение и экопотребление. Детерминантами проэкологического поведения в России является пол (женский), уровень образования (высшее), биосферические ценности, экологическая обеспокоенность, экологическая мотивация, личные и дескриптивные нормы. В дальнейшем необходимо расширять российскую базу научных знаний о проэкологическом поведении и его детерминантах за счет проведения лабораторных и естественных экспериментов, а также повышать качество методологии сбора и анализа данных.